Incidence, prevalence and clinical presentation of inflammatory bowel diseases in Northern France: a 30-year population-based studyResearch in context - Hélène Sarter; Thibaut Crétin; Guillaume Savoye; Mathurin Fumery; Ariane Leroyer; Luc Dauchet; Thierry Paupard; Hugues Coevoet; Pauline Wils; Nicolas Richard; Dominique Turck; Delphine Ley; et al. (Elsevier, 2024)
Summary: Background: In industrialized countries, the incidence of inflammatory bowel disease (IBD) appears stabilized. This study examined the incidence and phenotype of IBD in Northern France over a 30-year period. Methods: Including all IBD patients recorded in the EPIMAD population-based registry from 1988 to 2017 in Northern France, we described the incidence and clinical presentation of IBD according to age, sex and time. Findings: A total of 22,879 incident IBD cases were documented (59% (n = 13,445) of Crohn's disease (CD), 38% (n = 8803) of ulcerative colitis (UC), 3% (n = 631) of IBD unclassified (IBDU)). Over the study period, incidence of IBD, CD and UC was 12.7, 7.2 and 5.1 per 105 person-years, respectively. The incidence of CD increased from 5.1/105 in 1988-1990 to 7.9/105 in 2015-2017 (annual percent change (APC): +1.9%, p < 0.0001). The incidence of UC increased from 4.5/105 to 6.1/105 (APC: +1.3%, p < 0.0001). The largest increase was observed in children (+4.3% in CD, p < 0.0001; +5.4% in UC, p < 0.0001) followed by young adults aged 17-39 years (+1.9% in CD, p < 0.0001; +1.5% in UC, p < 0.0001). The increase in UC incidence was significantly higher in women than in men (+1.9% in women, +0.8% in men; p = 0.006). We estimated that in our area, by 2030, nearly 0.6% of the population will have IBD. Interpretation: The persistent increase of IBD incidence among children and young adults but also in women with UC in Northern France, suggests the persistence of substantial predisposing environmental factors. Funding: Santé Publique France; INSERM; Amiens, Lille and Rouen University Hospitals.